HUBUNGAN INDEKS MASSA TUBUH DENGAN DERAJAT KEPARAHAN CEDERA LIGAMEN LUTUT ANTERIOR - Rafi Achsan Ismail; Nuryani Sidarta (Fakultas Kedokteran Universitas Trisakti, 2026)
Anterior cruciate ligament injury was a common knee injury that could cause joint instability and functional impairment. This ligament played an essential role in maintaining knee stability by preventing anterior movement of the tibia. Anterior cruciate ligament injury was classified into three grades based on the severity of the ligament tear, ranging from mild injury without functional disturbance to complete rupture causing significant knee instability. Body mass index was considered a potential factor that might have influenced the severity of anterior cruciate ligament injury. This study aimed to determine the relationship between body mass index and the severity of anterior cruciate ligament injury. This study used an analytic survey method with a cross sectional approach. The sample consisted of secondary data obtained from medical records of patients diagnosed with anterior cruciate ligament injury at Jakarta Hospital from January 2022 to July 2025, with a total of 58 subjects. Data were analyzed using the Fisher test. The results showed that the most common severity of anterior cruciate ligament injury was grade two. Statistical analysis indicated that there was no significant relationship between body mass index and the severity of anterior cruciate ligament injury. In conclusion, body mass index was not significantly associated with the severity of anterior cruciate ligament injury.